Psychometric properties of the Italian oldenburg burnout inventory (student version) and measurement invariance with the USA - Loscalzo, Yura; Rice, Kenneth G.; Giannini, Marco (Current psychology (New Brunswick, N.J.), 2024)
Burnout has been studied extensively in work-related contexts and more recently investigated in academic settings. The present study aimed to analyze the psychometric properties of the student version of the Oldenburg Burnout Inventory (OLBI-S; Reis et al., 2015 ) on an Italian sample of university students ( n = 339, M age = 22.67 ± 4.10), and its measurement invariance with a USA sample ( n = 553, M age = 23.47 ± 5.96). Separate sample analyses provided psychometric support for 14 but not all 16 of the original OLBI-S items. Cross-sectional model comparisons supported partial metric invariance for the 14-item OLBI-S items when comparing the Italian and USA samples. However, scalar invariance was not supported. Finally, we found good internal reliability, and convergent, concurrent, and discriminant validity for the 14-item Italian OLBI-S. Hence, results supported using the 14-item OLBI-S in future studies of academic burnout in Italian and USA samples, and as a possible screening instrument to identify students experiencing burnout, especially during academic periods associated with higher stress. However, the 14-item OLBI-S should not be used to compare levels of burnout factors between Italian and USA students due to the lack of scalar invariance. Future work could entail further scale revisions or the development of burnout measures specifically related to the academic context rather than adapting work-related burnout scales to the study area.